2009
DOI: 10.1007/s11894-009-0035-1
|View full text |Cite
|
Sign up to set email alerts
|

Current perspectives on pediatric intestinal transplantation

Abstract: Irreversible intestinal failure in children is predominantly caused by surgical conditions such as volvulus, necrotizing enterocolitis, and gastroschisis. Functional intestinal failure from motility disorders such as intestinal pseudo-obstruction or enterocyte dysfunction with microvillus inclusion disease also may require intestine replacement. Approved indications for intestinal transplantation include liver dysfunction, loss of major venous access, frequent central line-related sepsis, and recurrent episode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 48 publications
0
21
0
Order By: Relevance
“…The University of Pittsburgh, a large transplant center, performed 169 intestinal allografts from May 1990 to December 2008, including 98 liver-intestine and 71 isolated intestinal transplants with reported 1-, 3-, and 5-year patient survival (for intestinal transplants and liver/small intestinal transplants combined) of 95%, 84%, and 77%, respectively, with corresponding graft survival rates of 88%, 74%, and 58%, respectively [9]. Another center reported that the graft survival for all intestinal transplant patients at 1 year was 80% for isolated small bowel and 70% for liver/small bowel.…”
Section: Discussionmentioning
confidence: 99%
“…The University of Pittsburgh, a large transplant center, performed 169 intestinal allografts from May 1990 to December 2008, including 98 liver-intestine and 71 isolated intestinal transplants with reported 1-, 3-, and 5-year patient survival (for intestinal transplants and liver/small intestinal transplants combined) of 95%, 84%, and 77%, respectively, with corresponding graft survival rates of 88%, 74%, and 58%, respectively [9]. Another center reported that the graft survival for all intestinal transplant patients at 1 year was 80% for isolated small bowel and 70% for liver/small bowel.…”
Section: Discussionmentioning
confidence: 99%
“…ACR is determined in the first 3 months. The historic incidence of ACR (80%) has improved to 20-50% (6,(8)(9)(10)(11). The level of ACR has declined following the use of rATG (4,12).…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of CMV infection was reported at about 14% to 25% (6,11). We encountered one case of invasive CMV infection, and it was treated by IV ganciclovir.…”
Section: Original Articlementioning
confidence: 95%
“…In one study, the 1-, 3-and 5-year patient survival of 199 children who were transplanted in Pittsburgh in the new era is 95%, 84%, and 77%, respectively. Graft survival was 88%, 74%, and 58%, respectively [55]. Poor prognostic markers included children younger than 1 year of age, no induction therapy with interleukin-2 blockers, and waiting in hospital before transplant [56].…”
Section: Graft Rejectionmentioning
confidence: 99%